2012
DOI: 10.1177/0898010112453325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Therapeutic Touch on Anxiety, Vital Signs, and Cardiac Dysrhythmia in a Sample of Iranian Women Undergoing Cardiac Catheterization

Abstract: TT is an effective approach for managing state anxiety, regulating vital signs, and decreasing the incidence of cardiac dysrhythmia during stressful situations, such as cardiac catheterization, in Iranian cardiac patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
1
17
0
5
Order By: Relevance
“…The study also found that 65.27% of patients awaiting coronary angiography are anxious. This result is consistent with those obtained by Ganji et al [5], Zolfagari et al [26], Ruffiningo et al [15], Hamel et al [7] and Uzun et al [9], indicating that the coronary angiography procedure causes anxiety in many patients. Conducted research in this field shows that in more than 82 percent of the patients who have undergone this procedure, fear and anxiety occurs due to performing this procedure and the results of diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…The study also found that 65.27% of patients awaiting coronary angiography are anxious. This result is consistent with those obtained by Ganji et al [5], Zolfagari et al [26], Ruffiningo et al [15], Hamel et al [7] and Uzun et al [9], indicating that the coronary angiography procedure causes anxiety in many patients. Conducted research in this field shows that in more than 82 percent of the patients who have undergone this procedure, fear and anxiety occurs due to performing this procedure and the results of diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…Na literatura cientifica, boa parte das pesquisas envolvendo o uso do Toque Terapêutico retrata um tratamento direcionado aos sintomas psicossomáticos. 8,9,22,27 Krieger 11 aponta que dentre os sistemas orgânicos mais sensíveis ao Toque Terapêutico, destaca-se o sistema nervoso autônomo.…”
Section: Resultados Da Seleção Dos Artigosunclassified
“…Destacam-se nessa política a acupuntura, a homeopatia, a fitoterapia e a medicina antroposófica. Por outro lado, o Toque Terapêutico, uma modalidade de terapia complementar que, segundo a literatura científica, 7,8,9 apresenta efetividade significativa sobre o tratamento de diversas doenças, não faz parte da PMNPC, embora nas últimas décadas venha ocorrendo um crescente interesse na investigação científica evolvendo o uso desta modalidade de terapia complementar. 10 O Toque Terapêutico é uma versão contemporânea de antigas práticas de cura por meio da imposição de mãos sobre o campo energético humano (CEH), que tem como ponto de referência para o início de sua utilização os estudos desenvolvidos por Dolores Krieger e Dora Kunz na década de 1970.…”
Section: Introductionunclassified
“…Benzer şekilde diğer bir çalışmada ise koroner bypass ameliyatı öncesi uygulanan terapötik dokunmanın kan basıncına olumlu etkisinin olmadığı fakat solunum ve nabzı düşürdüğü belirlenmiştir [32]. İranlı kadın hastalara kalp kateterizasyonu öncesinde uygulanan terapötik dokunmanın yaşam bulgularını normal seviyede tuttuğu ve aritmi oluşumunu azalttığını saptanmıştır [15]. Çalışma bulguları literatür ile benzerdir.…”
Section: Discussionunclassified
“…Terapötik dokunmanın psikiyatri hastalarında [11], yanıklı hastalarda [12], koroner arter bypass greft ameliyatı yapılan hastalarda [13], yaşlılarda [14] ve kalp kateterizasyonu yapılacak hastalarda [15] ağrı ve kaygıyı azaltmada etkili olduğu saptanmıştır.…”
Section: Introductionunclassified